The role of Pilates method in the elderly’s cognition and self-image: Systematic review (Research, Society and Development, 2021)
The Pilates method is an exercise system that pursuit an improvement in flexibility, physical resistance, strength, balance, and motor coordination. Furthermore, it is generally agreed that the method can contribute to the improvement of cognitive and self-image patterns of the elderly, for the practitioner needs to perform the exercises consciously and fluidly. This systematic review aimed to evaluate the role of the Pilates method in the cognition and self-image of the elderly. It was done two systematic reviews in BVS, Pubmed/Medline, Scielo, Web of Science, Cochrane, Eric, Capes, and PsycINFO databases, between 2009 and 2019. As a result, two articles were found on Pilates' practice on cognition in the elderly. These studies evidenced an improvement in the cognitive function and general function of elderly practitioners of the method. About the relationship between Pilates, self-image, and the elderly, no article was found. Thereby, it appears the need for more studies that contemplate the relation of cognition and self-image in the elderly practitioners of the Pilates method, for they are factors that help in personal development and quality of life.